Reproductive behaviour of families segregating for Cooley's anaemia before and after the availability of prenatal diagnosis. Issue 8 (August 1991) - Gamberini, M R; Lucci, M; Vullo, C; Anderson, B; Canella, R; Barrai, I
Abstract : The reproductive behaviour of couples with heterozygous beta thalassaemia, with at least one affected child, was investigated for the period 1955 to 1984 and was compared to the behaviour of control couples matched for age, age at marriage, and presence of at least one child. The comparisons were made as a function of knowledge of the risk and availability of prenatal diagnosis and abortion. It was found that the couples segregating for Cooley's anaemia, before knowledge of the risk, had a higher reproductive rate than that of control couples. Knowledge of the genetic risk had a different effect on reproductive behaviour in the 1950s from that in later years. The difference was attributed both to the influence of cultural factors and to technical, therapeutic, and diagnostic advances.